First record of the spatial organization of the nucleosome‐less chromatin of dinoflagellates: The nonrandom distribution of microsatellites and bipolar arrangement of telomeres in the nucleus of Gambierdiscus australes (Dinophyceae). Issue 2 (9th February 2022) - Cuadrado, Ángeles; Figueroa, Rosa I.; Sixto, Marta; Bravo, Isabel; De Bustos, Alfredo
Abstract : Dinoflagellates are a group of protists whose exceptionally large genome is organized in permanently condensed nucleosome‐less chromosomes. In this study, we examined the potential role of repetitive DNAs in both the structure of dinoflagellate chromosomes and the architecture of the dinoflagellate nucleus. Non‐denaturing fluorescent in situ hybridization (ND‐FSH) was used to determine the abundance and physical distribution of telomeric DNA and 16 microsatellites (1‐ to 4‐bp repeats) in the nucleus of Gambierdiscus australes . The results showed an increased relative abundance of the different microsatellite motifs with increasing GC content. Two ND‐FISH probes, (A)20 and (AAT)5, did not yield signals whereas the remainder revealed a dispersed but nonrandom distribution of the microsatellites, mostly in clusters. The bean‐shaped interphase nucleus of G. australes contained a region with a high density of trinucleotides. This nuclear compartment was located between the nucleolar organizer region (NOR), located on the concave side of the nucleus, and the convex side. Telomeric DNA was grouped in multiple foci and distributed in two polarized compartments: one associated with the NOR and the other peripherally located along the convex side of the nucleus. Changes in the position of the telomeres during cell division evidenced their dynamic distribution and thus that of the chromosomes during dinomitosis. These insights into the spatial organization of microsatellites and telomeres and thus into the nuclear architecture of G. australes will open up new lines of research into the structure and function of the nucleosome‐less chromatin of dinoflagellates.